2003
DOI: 10.1124/mol.63.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 Mitogen-Activated Protein Kinase and Activator Protein-1 during the Promotion of Neurite Extension of PC-12 Cells by 15-Deoxy-Δ12,14-prostaglandin J2

Abstract: 15-Deoxy-⌬12,14 -prostaglandin J 2 (15-deoxy-PGJ 2 ), a naturally occurring ligand, activates the peroxisome proliferator-activated receptor-␥ (PPAR-␥). Activation of PPAR-␥ has been found to induce cell differentiation in such cells as adipose cells and macrophages. Herein, we investigated whether 15-deoxy-PGJ 2 has neuronal cell differentiation and possible underlying molecular mechanisms. Dopaminergic differentiating PC-12 cells treated with 15-deoxy-PGJ 2 (0.2 to 1.6 M) alone showed measurable neurite exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…49,50 15-Deoxy-PGJ2, a metabolite of prostaglandin D2 and a ligand of peroxisome proliferatorsactivated receptor-␥, is known to induce neurite outgrowth in PC12 cells via activation of p38MAP kinase in conjunction with the AP-1 signal pathway. 51,52 Regulation of dynamics of actin filament by agents such as jasplakinolide that induce actin polymerization by enhancing actin filament nucleation 53 has also been shown to be crucial for neurite outgrowth. 54 In our hands, addition of forskolin but none of the other agents attenuated the inhibitory effect by myocilin overexpression on neurite outgrowth ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…49,50 15-Deoxy-PGJ2, a metabolite of prostaglandin D2 and a ligand of peroxisome proliferatorsactivated receptor-␥, is known to induce neurite outgrowth in PC12 cells via activation of p38MAP kinase in conjunction with the AP-1 signal pathway. 51,52 Regulation of dynamics of actin filament by agents such as jasplakinolide that induce actin polymerization by enhancing actin filament nucleation 53 has also been shown to be crucial for neurite outgrowth. 54 In our hands, addition of forskolin but none of the other agents attenuated the inhibitory effect by myocilin overexpression on neurite outgrowth ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…JNK activity also is regulated by phosphorylation by various upstream MAPK kinases (46). Positive and negative effects of 15d-PGJ 2 on ERK, JNK, and p38 MAPK activities have been reported (37,(47)(48)(49)(50). These effects result in the regulation of the level of phosphorylation and activation of AP-1 components.…”
mentioning
confidence: 99%
“…15d-PGJ 2 has been shown to exert its effect through the activation of the nuclear receptor peroxisome proliferator-activated receptor-γ (PPAR γ ) (1,4) and the classical PGD 2 receptor (DP) (5). However, in PC12 cells, neither PPAR γ antagonist nor DP antagonist have been shown to affect the 15d-PGJ 2 enhancement of NGF-induced neurite outgrowth (3). Therefore, the mechanism by which 15d-PGJ 2 activates NGF-induced neurite outgrowth is unknown.…”
Section: -Deoxy-δmentioning
confidence: 99%
“…Jung et al demonstrated that in PC12 cells, the 15d-PGJ 2 enhancement of NGF-induced neurite outgrowth depends on activation of p38 MAP kinase and not activations of PPAR γ , DP, or PGE 2 receptor, which suggests that the promoting effect of 15d-PGJ 2 may not be mediated by cell surface G-protein-coupled receptors (3). Here, we demonstrated that the CRTH2 antagonist CAY10471 can inhibit both the promoting effect of 15d-PGJ 2 on NGF-induced neurite outgrowth and 15d-PGJ 2 -induced phosphorylation of p38 MAP kinase.…”
Section: -Deoxy-δmentioning
confidence: 99%
See 1 more Smart Citation